2012
DOI: 10.1042/bj20120509
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial c-Src regulates cell survival through phosphorylation of respiratory chain components

Abstract: Mitochondrial protein tyrosine phosphorylation is an important mechanism for the modulation of mitochondrial functions. In the present study, we have identified novel substrates of c-Src in mitochondria and investigated their function in the regulation of oxidative phosphorylation. The Src family kinase inhibitor PP2 {amino-5-(4-chlorophenyl)-7-(t-butyl) pyrazolo [3,4d] pyrimidine} exhibits significant reduction of respiration. Similar results were obtained from cells expressing kinase-dead c-Src, which harbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 41 publications
5
89
0
1
Order By: Relevance
“…are thus consistent with a model in which TRAP1 regulates the previously reported ability of mitochondrial c-Src to stimulate oxidative phosphorylation (14,15). Reduced/absent TRAP1 expression also correlates with increased cell motility/invasiveness that is sensitive to c-Src inhibition and ROS buffering strategies.…”
supporting
confidence: 75%
See 4 more Smart Citations
“…are thus consistent with a model in which TRAP1 regulates the previously reported ability of mitochondrial c-Src to stimulate oxidative phosphorylation (14,15). Reduced/absent TRAP1 expression also correlates with increased cell motility/invasiveness that is sensitive to c-Src inhibition and ROS buffering strategies.…”
supporting
confidence: 75%
“…Miyazaki et al first reported that c-Src is located within mitochondria and affects energy metabolism by phosphorylating complex IV (14). Later studies confirmed that c-Src is present in the inner mitochondrial membrane/matrix (15). Although the mechanism by which TRAP1 regulates mitochondrial c-Src is not yet clarified, the cytosolic c-Src-HSP90 interaction provides a model to address this question.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations